PKM Pelatihan Promosi Penjualan pada Pedagang di Tonggimoncong - Mustari Mustari; Ilham Thaef; M. Ihsan Said Ahmad (DEDIKASI, 2020)
The purpose of the training is to provide insight, knowledge, and practice to merchants in Tinggimoncong, Gowa Regency as participants in sales promotion training, so that they can develop their own methods or methods in sales promotion and can run their business according to the plans that have been drawn up which lead to achieving goals. . The benefit of the training activity is that participants can implement sales promotions in the business according to their wishes and obtain the merchant's business performance as expected.This service activity was attended by 20 traders in Tinggi Moncong, Gowa Regency. There were several participants who previously registered themselves to take part in this activity, but the participants were unable to attend at the time of implementing the activity. The training participants were very enthusiastic about participating in this activity, as evidenced by their timely arrival. Enthusiasm was also seen in listening to the explanations from the speakers and the many questions asked about the material given. Although at the end of the activity session a special time was provided for question and answer, some participants also asked questions in the middle of the material given. The implementation of sales promotion training in order to increase sales of merchants in Tinggi Moncong, Gowa Regency can increase their sales results in the future. For traders, using and implementing effective sales promotion methods and methods has implications for their sales results. And become part of the prospect as a necessity in the interaction. This has become a positive value for traders in doing business because they are able to make friends with many people and try to build networks in their trading business. This is a strength as well as an opportunity that can be reached and useful for introducing and offering products to prospective buyers which have implications for increasing their merchandise.